Asuhan Keperawatan Pada Pasien Dengan Penyakit Jantung Koroner (Pjk) Di Ruang High Care Unit (Hcu) Di Rsud Padang Pariaman - Rintan Rahmawati; Debby Silvia Dewi; Mike Asmaria; Hilma Yessi (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Based on data from the World Health Organization, cardiovascular disease is the leading cause of death, worldwide, as many as 19.8 million people died from cardiovascular disease and 38% of these deaths were caused by Coronary Heart Disease (CHD). Based on data from the Indonesian Health Survey, Coronary Heart Disease caused death, as much as 0.85% or as many as 765,000 cases. From the survey results, West Sumatra is ranked 10th in the provinces with Coronary Heart Disease with a prevalence of 0.87%. Based on data obtained at Padang Pariaman Regional Hospital, Coronary Heart Disease cases were ranked 15th in 2025 with 56 cases. This case study aims to obtain an overview of the application of nursing care to patients with Coronary Heart Disease, including use, establishing nursing diagnoses, planning nursing, carrying out, implementing, evaluating, acting and documenting. The methods, data collection used in this case study are observation interviews, physical examinations and medical records. This case study was conducted in the HCU room of Padang Pariaman Regional Hospital from February 25 to March 1, 2026. The results of the study obtained nursing problems in the form of ineffective breathing patterns, decreased cardiac output, fatigue, acute pain and the risk of ineffective peripheral perfusion. Nursing problems were resolved on the 5th day with nursing actions provided in the form of airway management, cardiac care, pain management, susigi management and shock prevention. It can be concluded that the treatment of Coronary Heart Disease patients requires medical action and patient awareness in managing lifestyles to improve the quality of nursing care in hospitals. It is hoped that patients and their families can understand the importance of awareness in maintaining a healthy lifestyle to prevent complications due to Coronary Heart Disease.